Preparation and Characterization of Highly Water Soluble Curcumin – Dextrose Cocrystal - Katherine Kho; Denny Nugroho; Asaf Kleopas Sugih (The Journal of Pure and Applied Chemistry Research, 2018)
Curcumin is a natural food colorant isolated from rhizomes of turmeric (Curcuma longa). Despite its many favorable properties, curcumin is practically insoluble in water and relatively unstable, thus limiting its application. In this research, a potential method to improve curcumin solubility and stability, i.e. cocrystallisation of curcumin with dextrose was investigated.. The effect of curcumin content in the cocrystals on solubility and yield of the product was studied. The morphology of the cocrystals was observed using SEM. In addition, stability in different pH range was investigated.  Crystal structure and curcumin – dextrose interaction were analyzed using FT-IR spectra and DSC thermograms. The result shows that curcumin – dextrose cocrystal is a potential food colorant that could be applied to water – based food at various pH range.